ASUPAN ZAT GIZI MAKRO DAN STATUS GIZI REMAJA DI SMA NEGERI 5 PONTIANAK - Yustita Pira, Yustita Pira; Nopriantini, Nopriantini; Didik Hariyadi, Didik Hariyadi (Jurnal GIZIDO, 2024)
Research objectives: This study aims to determine the description of macronutrient intake and nutritional status of adolescents at SMA Negeri 5 Pontianak. Method: This research method is descriptive, namely a research subject where observations and measurements are carried out at the same time. Population: The population of this study were class X students at SMA Negeri 5 Pontianak with a total population of 150 people. Sample: There were 60 research samples obtained. Instrument: Research instruments using informed consent sheets, digital stepping scales, microtoises, food recall forms, and food models. Results: Research conducted on class 26 people (43%) had less protein and less than 35 people (58.3%). Conclusion: It can be concluded that the majority of teenagers in the good nutritional status category are 66.6%, 16.6% are undernourished, 13.4% are overnourished and 3.4% are obese. In the category of 63.4% less carbohydrate intake, 43% less protein intake and 58.3% less fat intake.